Educator mental health literacy to scale: from theory to practice. Issue 1 (2nd January 2017) - Fortier, Alexandra; Lalonde, Gail; Venesoen, Philippe; Legwegoh, Alexander F.; Short, Kathryn H.
Abstract: Schools are an excellent setting through which to promote mental health and well-being, and teachers are well positioned to provide related instruction and support in the classroom. However, teachers often report that they lack the knowledge, skills and confidence to deliver social emotional learning instruction and to support students who struggle with mental health challenges. Professional learning initiatives that build teacher capacity in this area are increasing in quantity, but not all of the offerings are evidence based, relevant, scalable, and sustainable. This paper explores the approach being implemented in school districts within Ontario, Canada to enhance mental health literacy for educators. A description of the mental health literacy strategy within the Thames Valley District School Board is provided to illustrate how school districts can align with broad directions while at the same time contextualizing efforts to address local priorities and perspectives. The paper offers a synthesis of lessons learned from this early adopter case study, and from the implementation of the broader provincial approach.